High Temperature Membrane Reactor System for Hydrogen Permeation Measurements and Validation with Pd Based Membranes - Badwal, S. P.S.; Ciacchi, F.T. (Journal of Membrane and Separation Technology, 2013)
Hydrogen separation membranes are under development for integration with a coal gasifier or natural gas reformer for pre-combustion separation of hydrogen and carbon dioxide. Because of the high operating temperatures and pressures, a robust reactor and associated control systems are required for fast screening of membrane materials with a strong emphasis on operator and plant safety. In this paper, the design, construction and commissioning of a reliable membrane reactor and a versatile test station for evaluation of hydrogen permeation membrane materials (metals, ceramics or cermets) at high temperatures and high differential pressures has been described. The membrane reactor system has been designed to operate at temperatures up to 800oC and pressure differentials across the membrane to 1.0MPa. The system has multiple levels of safety redundancy built-in which include a range of controls and monitors for both operator and system safety. A number of Pd and Pd-Ag alloys of nominal thicknesses in the 20 and 140µm range were sourced and alumina based porous ceramic support structure were fabricated for evaluation of metal membranes. The test station has been validated with Pd and Pd-Ag alloys of different thicknesses. The data obtained from the reactor for various membrane types and thicknesses are in agreement with those reported in the literature.